Diagnosis and Management of a Patient With Chronic Lymphocytic Leukemia and a Concurrent Plasmacytoma - Danielle C. Thor; Rohan Umrani; Jack Bergal; Charles Yang; Richard Gordon (Case Reports in Oncological Medicine)
Chronic lymphocytic leukemia (CLL) typically presents as an indolent disease with a benign disposition in most patients. In select patients, CLL can progress into a more aggressive disease via its original morphology, following a Richter transformation to an alternative non-Hodgkin’s lymphoma, or with the concomitant development of multiple myeloma. In an extremely rare subset of individuals with CLL, an extramedullary plasmacytoma may coexist. This case report seeks to describe the diagnosis and treatment of a patient with concurrent CLL and a plasmacytoma.